Acute Hydrocephaly Following Methadone Intoxication in a Child - FAYYAZI, Afshin; KHAJEH, Ali; BAGHERI, Mohamad; AHMADI, Sina (Iranian Journal of Child Neurology, 2012)
How to Cite this Article: Fayyazi A, Khajeh A, Bagheri M, Ahmadi S. Acute Hydrocephaly Following Methadone Intoxication in a Child. Iranian Journal of ChildNeurology 2012;6(1):35-38. Infantile methadone intoxication has been on the rise since the usage of methadone in opioid detoxification programs. We report a 30-month-old child with encephalopathy and acute hydrocephaly following methadone intoxication. References: 1. Nazari H. Clinical approach to methadone toxication.Quarterly journal of Addiction 2007;2:18-20. 2. Plummer JL, Gourlay GK, Cherry DA, Cousins MJ.Estimation of methadone clearance: application in themanagement of cancer pain. Pain 1988 Jun;33(3):313-22. 3. Davies D, DeVlaming D, Haines C. Methadoneanalgesia for children with advanced cancer. PediatrBlood Cancer 2008 Sep;51(3):393-7. 4. Riascos R, Kumfa P, Rojas R, Cuellar H, Descartes F.Fatal methadone intoxication in a child. Emerg Radiol2008 Jan;15(1):67-70. 5. Binchy JM, Molyneux EM, Manning J. Accidental ingestion of methadone by children in Merseyside.BMJ 1994 May 21;308(6940):1335-6. 6. Li L, Levine B, Smialek JE. Fatal methadone poisoningin children: Maryland 1992-1996. Subst Use Misuse2000 Aug;35(9):1141-8. 7. Milroy CM, Forrest AR. Methadone deaths: atoxicological analysis. J Clin Pathol 2000 Apr;53(4):277-81. 8. Afzali S, Jafari MR. One year study of chest X-raychanges in opiate-poisoned patients in Hamadan. JQom Uni Med Sci 2010; 4(2):3-7. 9. Zamani N, Sanaei-Zadeh H, Mostafazadeh B. Hallmarksof opium poisoning in infants and toddlers. Trop Doct2010 Oct; 40(4):220-2. 10. Besharat S, Besharat M, Akhavan Masouleh A, JabbariA, Yazdi HR. Opium intoxication in children under 5years old, Golestan- Iran (2006-07). J Gorgan Uni MedSci Spring 2010;12(1):85-9. 11. Izadi Mood N, Gheshlaghi F, Sharafi SE. Fatalpoisoning cases admitted to the emergency departmentof poisoning, Noor Hospital, Isfahan. J Legal Med IslRep Iran 2003;9(31):122-26. 12. Boushehri B, Yekta Z, Zareei-Kheirabad A, Kabiri SH,Kazempour A. Determining the frequency of poisoningwith chemical agents and drugs in hospitalized patientsof Taleghani Hospital Uromieh, 2001-2004. J LegalMed Isl Rep Iran2004;10(35):126-131. 13. Cheraghali F, Taymori M. Epidemiological study ofdrug intoxication in children. Acta Medica Iranica2006;44(1):37-40. 14. Iran Ministry of Health report: some case reports ofoccasional methadone toxication in infants. QuarterlyJ Addiction 2007;2:26. 15. Geibprasert S, Gallucci M, Krings T. Addictiveillegal drugs: structural neuroimaging. AJNR Am JNeuroradiol 2010 May;31(5):803-8. 16. Malloy S, Soh C, Williams TL. Reversible delayed posthypoxic leukoencephalopathy. AJNR Am J Neuroradiol2006 Sep;27(8):1763-5. 17. Glatstein M, Finkelstein Y, Scolnik D. Accidentalmethadone ingestion in an infant: case report andreview of the literature. Pediatr Emerg Care 2009Feb;25(2):109-11.